Idiopatisk cystit hos katt : en retrospektiv studie - Johansson, Maria (SLU/Dept. of Animal Environment and Health (until 231231), 2006)
Lower urinary tract diseases are a common problem in cats all over the world. The symptoms are for example dysuria, pollakuria, stranguria, periuria and hematuria. In approximately two thirds of these cats the underlying cause is not known and the disease is therefore called feline idiopathic cystitis (FIC). We need to know more about the disease to get a consistently effective treatment and prevention.